Development and roll out of the JETS e-portfolio: a web based electronic portfolio for endoscopists. Issue 1 (20th November 2010) - Mehta, T; Dowler, K; McKaig, B C; Valori, R M; Dunckley, P
Abstract : The JAG Endoscopy Training System (JETS) e-portfolio was designed to provide an electronic log of endoscopic experience, improve the effectiveness of training, streamline the JAG certification process and support the quality assurance of trainers, units and regional training programmes. It was piloted in 2008 with an 82.6% uptake in trainees offered the system. The system was released in the UK in September 2009. Steady adoption across the UK demonstrates the service finds it a valuable tool. In time it will be the only vehicle through which a trainee can achieve certification through JAG to practise independently.